2020
DOI: 10.1177/0013916519896868
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Household Water Conservation Interventions Using the Information–Motivation–Behavioral Skills Model

Abstract: Increasing droughts and water shortages are intensifying the need for residential water conservation. We identify and classify 24 water conservation studies using the information–motivation–behavioral skills (IMB) model by categorizing interventions based on content and water conservation effectiveness. This synthesis revealed several insights. First, all of the interventions used information, motivation, and/or behavioral skills, suggesting that water conservation interventions can be interpreted within the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 104 publications
3
41
1
Order By: Relevance
“…Second, a mailer may be a weak method to effectively educate households about behavioral skills. Nonetheless, this and similar studies report positive effects (also see recent review of messaging interventions, Ehret et al., 2020). Third, the mailings were limited by an inability to measure whether all members of the household saw the treatment or how often.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Second, a mailer may be a weak method to effectively educate households about behavioral skills. Nonetheless, this and similar studies report positive effects (also see recent review of messaging interventions, Ehret et al., 2020). Third, the mailings were limited by an inability to measure whether all members of the household saw the treatment or how often.…”
Section: Discussionsupporting
confidence: 54%
“…Second, the IMB model (Fisher & Fisher, 2000) provides a theoretical foundation that is congruent with the message content that water districts typically send: 1) general information about a problem (e.g., whether there is a drought), 2) motivating messages, and 3) suggestions for specific behaviors. A recent review of published water conservation studies showed that all messaging interventions designed to reduce water used some components of information, motivation, and behavioral skills even though none of the studies were explicitly informed by the IMB framework (Ehret et al., 2020).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to two discomfiting claims: behaviors that impact the environment are rarely explained by a conscious motivation towards nature, and conservation efforts will fail if the damaging behavior is easier, cheaper, or better serves social motives. Even deliberate conservation actions could be explained through core social motives (review; [88]), and meta-analyses suggest that the most effective interventions harness motives such as belongingness [24].…”
mentioning
confidence: 99%